2016
DOI: 10.1002/jor.23381
|View full text |Cite
|
Sign up to set email alerts
|

Autologous tendon-derived cell-seeded nanofibrous scaffolds improve rotator cuff repair in an age-dependent fashion

Abstract: Rotator cuff tendon tears are one of the most common shoulder pathologies, especially in the aging population. Due to a poor healing response and degenerative changes associated with aging, rotator cuff repair failure remains common. Although cell-based therapies to augment rotator cuff repair appear promising, it is unknown whether the success of such a therapy is age-dependent. We hypothesized that autologous cell therapy would improve tendon-to-bone healing across age groups, with autologous juvenile cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In the second release study, BiLDS and BiLDS_IBP were incubated on a shaker at Animals were anesthetized via inhalation of 5% isoflurane and maintained at 2% to 3% throughout surgery. Supraspinatus detachment was performed as previously described using sterile technique, 18,19 were stored in −20°C prior to thawing for quasi-static mechanical testing.…”
Section: In Vitro Release and Cell Studiesmentioning
confidence: 99%
“…In the second release study, BiLDS and BiLDS_IBP were incubated on a shaker at Animals were anesthetized via inhalation of 5% isoflurane and maintained at 2% to 3% throughout surgery. Supraspinatus detachment was performed as previously described using sterile technique, 18,19 were stored in −20°C prior to thawing for quasi-static mechanical testing.…”
Section: In Vitro Release and Cell Studiesmentioning
confidence: 99%
“…A plethora of different scaffolding materials are under investigation. Studies have shown that these scaffolds facilitate improved healing and mechanical stability and presentably fit the needs of regenerating tendons better than allografts [ 61 65 ]. Sharif-Aghdam et al prepared a modified silk nanoscaffold that demonstrated excellent collagen content production and viability [ 66 ].…”
Section: Sports Medicinementioning
confidence: 99%
“…Sharif-Aghdam et al prepared a modified silk nanoscaffold that demonstrated excellent collagen content production and viability [ 66 ]. Huegel et al showed that rat shoulders treated with autologous nanoscaffolds during supraspinatus repair surgery exhibited improved healing and mechanical stability [ 61 ]. Although tendon healing using nanotechnology has not yet reached the stage of clinical trials, research studies using tissue engineering techniques to simulate the bone-to-tendon interface are rampant [ 67 – 69 ].…”
Section: Sports Medicinementioning
confidence: 99%
“…Autologous tenocyte implementation (ATI) is a novel technique that has recently been used successfully in the treatment of a rotator cuff tear and tendinopathy [47]. This was a case study documenting a single participant; thus, it may not carry much statistical power.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Previous studies (Table 5) demonstrate that much of the research that examines human models demonstrated significant findings. However, there were no controls in five of the studies [38][39][40][41]47], which makes comparisons difficult since they will have to be made via comparison of histological data, giving room for different methodologies and techniques to influence results. Although the findings show that shoulder function has been improved, this could suggest that no matter which engineering approached is used, shoulder function will improve.…”
Section: Tissue Engineeringmentioning
confidence: 99%